Monte Carlo simulation for proton dosimetry in magnetic fields: Fano test and magnetic field correction factors kB for Farmer-type ionization chambers - Marot, Mathieu; Jäger, Fabian; Greilich, Steffen; Karger, Christian; Jäkel, Oliver; Burigo, Lucas Norberto (Physics in medicine and biology, 2023)
Objective. In this contribution we present a special Fano test for charged particles in presence of magnetic fields in the MC code TOol for PArticle Simulation (TOPAS), as well as the determination of magnetic field correction factors k B for Farmer-type ionization chambers using proton beams. Approach. Customized C++ extensions for TOPAS were implemented to model the special Fano tests in presence of magnetic fields for electrons and protons. The Geant4-specific transport parameters, DRoverR and finalRange, were investigated to optimize passing rate and computation time. The k B was determined for the Farmer-type PTW 30013 ionization chamber, and 5 custom built ionization chambers with same geometry but varying inner radius, testing magnetic flux density ranging from 0 to 1.0 T and two proton beam energies of 157.43 and 221.05 MeV. Main results. Using the investigated parameters, TOPAS passed the Fano test within 0.39 ± 0.15% and 0.82 ± 0.42%, respectively for electrons and protons. The chamber response (k B,M,Q) gives a maximum at different magnetic flux densities depending of the chamber size, 1.0043 at 1.0 T for the smallest chamber and 1.0051 at 0.2 T for the largest chamber. The local dose difference c B remained ≤ 0.1% for both tested energies. The magnetic field correction factor k B, for the chamber PTW 30013, varied from 0.9946 to 1.0036 for both tested energies. Significance. The developed extension for the special Fano test in TOPAS MC code with the adjusted transport parameters, can accurately transport electron and proton particles in magnetic field. This makes TOPAS a valuable tool for the determination of k B. The ionization chambers we tested showed that k B remains small (≤0.72%). To the best of our knowledge, this is the first calculations of k B for proton beams. This work represents a significant step forward in the development of MRgPT and protocols for proton dosimetry in presence of magnetic field.
Veröffentlicht: 29. August 2023
Gesehen am 27.10.2023